Measuring the harm of sugar sweetened beverages and internalities associated with it - Ding, Ningxin; Desai, Jaikishan (Frontiers in Public Health, 2024)
Obesity, partly driven by sugar-sweetened beverage (SSB) consumption, significantly raises the risk of type-2 diabetes and cardiovascular diseases, imposing substantial health and economic burdens. This study aims to measure the monetary value of health harm from SSB consumption, and the internalities associated with it, which are critical in determining the socially optimal tax rate. Using contingent valuation, we surveyed 293 Wellington, New Zealand residents on their willingness to pay (WTP) for reductions in diabetes, stroke, and heart disease risks associated with SSB intake. Logistic regression analysis revealed the marginal WTP for a 1% risk reduction in diabetes, stroke, and heart disease as 404.86, 809.04, and 1,236.84, respectively. Based on these values, our estimate shows the marginal harm from SSB consumption is approximately NZ17.37 per litre in New Zealand, with internalities of NZ6.43 per litre, suggesting an optimal tax rate of NZ6.49 per litre. Imposing such a tax would double or triple the price of SSBs in New Zealand.